Description of the early shell morphology of three species of Pectinidae (Mollusca: Bivalvia) from Argentina - Oviedo, Loreley; Pastorino, Guido (Zootaxa, 2023)
We describe the shell morphology of the prodissoconch and early postlarval shell of Aequipecten tehuelchus (d’Orbigny), Flexopecten felipponei (Dall), and Zygochlamys patagonica (King) from the southern coast of Argentina. Aequipecten tehuelchus has a nepioconch microsculpture with fine, dense, and regularly distributed pits. The byssal notch is initially deep and narrow but becomes sinuous at the beginning of the post-nepioconch. The nepioconch of Zygochlamys patagonica has antimarginal riblets; the byssal notch is wider than in A. tehuelchus and does not present the sinuosity observed in the other species. The microsculpture of the nepioconchs of F. felipponei and A. tehuelchus is indistinguishable. The earliest differentiation between the two species appears with the post-nepionic left valve, in which A. tehuelchus exhibits between 15 and 20 primary ribs while F. felipponei displays 28 to 34 faint folds. Zygochlamys patagonica shows 21 to 31 primary and secondary ribs. The taxonomic status of the three species is discussed in light of these findings and with respect to current adult-shell taxonomy and genetic analyses.